Masalah Perkembangan Psikis Pada Anak Usia Sekolah Dasar - Rani Nur Hidayah; Eolalia Fadya Trisnawati; Eka Ratna Istari Putri; Arrozika Sabrina Apriliana (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Child development issues in elementary school have a significant impact on the success of education and the child's future. At this age, children experience a crucial phase of development, where they not only grow physically, but also develop social, emotional, and cognitive skills. In this context, many factors can influence their psychological development, ranging from the family environment, parenting patterns, to the education system received. This study aims to explore the impact of external factors, such as bullying, parental expectations, and lack of social support. We emphasize the importance of early detection of symptoms of psychological problems and the active role of parents and teachers in creating an environment that supports children's mental health. In this study, we used a quantitative method with a document analysis approach. The results of this study identified several external factors that influence the development of elementary school-aged children. These factors include the family environment, parenting patterns, bullying, academic demands, social and economic factors, and the role of the community and school environment